See you in the cosmos - Cheng, Jack, 1983- (New York, NY : Dial Books, 2017)
"Eleven-year-old Alex Petroski, along with his dog, Carl Sagan, makes big discoveries about his family on a road trip and he records it all on a golden iPod he intends to launch into space"--
Keywords: Families -- Fiction; Voyages and travels -- Fiction; Dogs -- Fiction; JUVENILE FICTION / Family / Alternative Family; JUVENILE FICTION / Animals / Dogs; JUVENILE FICTION / People & Places / United States / Asian American